Differential Responses of Urinary Epinephrine and Norepinephrine to 24-h Shift-Work Stressor in Physicians - Boettcher, Claudia; Sommer, Grit; Peitzsch, Mirko; Zimmer, Klaus-Peter; Eisenhofer, Graeme; Wudy, Stefan A. (Frontiers in Endocrinology, 2020)
Multiple stressors, including 24-h-shifts characterise the working environment of physicians, influencing well-being, health and performance. We aimed to evaluate the effect of the stressor 24-h-shift on the adrenal medullary and sympathoneural system in physicians with the hypothesis that shift work might have different impacts on both systems. Twenty-two physicians collected two 12-h-urine samples (“daytime” and “nighttime”) during a 24h shift (“on-duty”) and on a free weekend (“off-duty”), respectively. Urinary excretion rates per m2 body surface area were assessed for the catecholamines epinephrine, norepinephrine and their respective free O-methylated metabolites metanephrine and normetanephrine by LC-MS/MS-analysis. The stressor provoked differential responses of epinephrine and norepinephrine. Epinephrine excretion rates showed significant increases from off to on duty. The largest proportional change (off-duty to on-duty) for epinephrine was observed for nighttime (205%), the increase for daytime was 84%. An increase in norepinephrine from off to on duty was only visible for nighttime collections. For the catecholamine metabolites, normetanephrine paralleled norepinephrine and exhibited an increase in excretion from off to on duty during nighttime collections of 53% whereas there was no change during daytime collections (3%). In conclusion: Whilst the 24-h-shift-work stressor in physicians activates the sympatho-adrenomedullary system, represented by epinephrine, the sympathoneural response through norepinephrine reflects mainly an ambulatory position during working hours.